The Cerebral Hemodynamic Response to Pain in Preterm Infants With Fetal Growth Restriction - Dix, Laura M. L.; Shepherd, Kelsee; Polglase, Graeme R.; Miller, Suzanne L.; Sehgal, Arvind; Wong, Flora Y. (Frontiers in Pediatrics, 2020)
Background: Preterm infants undergoing intensive care often experience painful procedures such as heel lance for blood sampling. Knowledge of the cerebral hemodynamic response to painful stimuli contributes to understanding of cortical pain processing and the neurovascular network in the preterm brain. Previous research has demonstrated cerebral hemodynamic responses using near-infrared spectroscopy (NIRS) after noxious stimuli in infants appropriately grown for age (AGA). But this has not been studied in infants born small for gestational age after fetal growth restriction (FGR). FGR infants differ in brain development due to utero-placental insufficiency leading to the intrauterine growth restriction, and cerebral response to pain may be altered. Objectives: We aimed to compare the cerebral hemodynamic response to painful stimuli (heel lance) in FGR and AGA infants. Methods: Preterm FGR infants (n = 20) and AGA infants (n = 15) born at 28–32 weeks' gestation were studied at mean ± SD postnatal age of 11.5 ± 2.4 and 10.5 ± 2.4 days, respectively. Infants had baseline echocardiographic assessment of ductus arteriosus and stroke volume. They were monitored with NIRS for changes in tissue oxygenation index (TOI, %), and oxygenated, deoxygenated, and total hemoglobin (ΔO2Hb, ΔHHb, and ΔTHb) in contralateral and ipsilateral cerebral hemispheres, during a heel lance. Results: At baseline, FGR infants had significantly lower TOI, higher heart rate, and lower stroke volume compared to AGA infants. Most infants in both groups showed increase in each of the NIRS parameters in the contralateral hemisphere following heel lance. However, more AGA infants (6/15) showed decreased ΔTHb compared to FGR infants (1/20) (p = 0.016). The magnitude of cerebral hemodynamic response and time to response did not differ between FGR and AGA infants. FGR infants showed larger ΔO2Hb in the contralateral compared to ipsilateral cortex (p = 0.05). Conclusion: Preterm FGR infants have reduced stroke volume and lower cerebral oxygenation compared to AGA infants in the second to third week of life. FGR infants show similar cerebral hemodynamic responses to noxious stimuli compared to AGA infants. However, FGR infants are less likely to have a cerebral vasoconstrictive response, possibly due to cerebrovascular changes following placental insufficiency and brain sparing in-utero.